Chemical utilisation of CO2 a challenge for the sustainable world - Jagadeesan, Dinesh; Joshi, Bhaskar; Parameswaran, Prashant (Resonance, 2015)
We derive more than 80% of our energy and chemicals from fossil fuels such as oil, coal and natural gas. Depleting resources and environmental pollution are forcing us to look for alternative resources. Carbon dioxide (CO2), which is produced in large quantities, could be recycled to chemical feedstocks.